Impact of extreme heat on health in Australia: a scoping review - Patrick Amoatey; Zhiwei Xu; Chinonso Christian Odebeatu; Neha Singh; Nicholas J. Osborne; Dung Phung (BMC Public Health)
Abstract Climate change has been recognized as a driver of increased heatwave events in the Asia Pacific region, including Australia. This review systematically retrieved and summarized published evidence on heat-related health impacts in Australia, focusing on heat-associated deaths, morbidity, and vulnerability. We searched PubMed, Scopus, Embase, and Web of Science for heat-health studies published in Australia between 2007 and 2023. A total of 64 articles met the inclusion criteria and were included in our review. Most were epidemiological studies [56 (87.5%)], which accumulatively considered 85 different cause-specific diseases linked to deaths, hospital admissions, emergency department (ED) presentations, and ambulance callouts, while eight studies focused on heat vulnerability index (HVI) assessment. We found strong evidence of increasing risks for heat-associated deaths among individuals with mental/behavioral disorders, cardiovascular diseases, diabetes, and respiratory disease. Evidence supporting an increasing risk for renal/genitourinary-related deaths was limited. The majority of studies reported an increase in heat-associated hospitalization, particularly for patients with renal disease, neurological disease, stroke, mental disorders, diabetes, and ischemic heart disease. Heat-associated ambulance callouts was prominent for patients with cardiovascular and respiratory diseases. This evidence suggests that these heat-related diseases should be used as health indicators for developing and validating HVI in Australia. Most studies did not examine the long-term changes in vulnerability and lacked evaluation with cause-specific health data. Future research must incorporate HVI across diverse climate change scenarios to more accurately inform long-term adaptation measures among vulnerable communities. In addition, research should target nationwide longitudinal heat vulnerability and examine the benefits of using HVI in heatwave action plans.